Determining suitable municipalities for establishing a fish processing plant in the southern part of Zamboanga del Sur province - Mochtar, Zainal Abidin (2007)
The main objective of this study was to identify the most suitable municipalities for establishing a fish processing plant in the southern part of Zamboanga del Sur (ZDS) province...